ASUHAN KEPERAWATAN PADA TN. S DENGAN CHRONIC KIDNEY DISEASE DI RSUD BANGKINANG - zianfadilla fadilla; Indrawati; Putri Eka Sudiarti; Nia Aprilla (El-Emir Institute, 2025)
CKD is a global health problem that continues to worsen. Data shows that CKD is the leading cause of death in the world. based on data from the last 1 month obtained from RSUD Bangkinang, there were 27 patients with CKD who were treated in the warrior room. one of the patients in the warrior room with a case of CKD was found